P2RY12-Inhibitors Reduce Cancer-Associated Thrombosis and Tumor Growth in Pancreatic Cancers - Palacios-Acedo, Ana Luisa; Mezouar, Soraya; Mège, Diane; Crescence, Lydie; Dubois, Christophe; Panicot-Dubois, Laurence (Frontiers in Oncology, 2021)
Platelet function can be “kidnaped” by cancer cells to support tumor growth, causing alterations in the delicate hemostatic equilibrium. This leads to a four-fold risk of thrombotic events in cancer patients, which in turn, portend poor prognosis. We previously demonstrated that anti-P2RY12 drugs inhibit thrombosis associated with cancer and formation of metastasis in pancreatic cancer models. We aimed to (1) Compare the effects of aspirin and known antiplatelet drug clopidogrel on pancreatic cancer prevention (2) Characterize the effects of known antiplatelet drug clopidogrel (platelet P2RY12 inhibitor) on cancer associated thrombosis and cancer growth in vivo (3) Determine the effect of P2RY12 across different digestive cancers in vitro and (4) Show a differential P2RY12 expression in two digestive cancer types. Clopidogrel treatment resulted in better survival rates with smaller primary tumors and less metastasis than aspirin treatment. Clopidogrel was also more effective than aspirin at dissolving spontaneous endogenous thrombi in our orthotopic cancer mouse model. P2RY12 expression gives pancreatic adenocarcinomas proliferative advantages, but not for colorectal cancer. Differential tumor P2RY12 expression could explain different pro-coagulation status of patients. In conclusion, the power to slow cancer spread of P2RY12 inhibitors warrants further studies to include it in current pancreatic cancer treatment panels. Clopidogrel can be used to target and prevent Trousseau’s syndrome with fewer side effects than aspirin.